Realist review of interprofessional education for health care students: What works for whom and why. Issue 2 (4th March 2023) - Maddock, Bronwyn; Dārziņš, Pēteris; Kent, Fiona
ABSTRACT: Interprofessional education (IPE) programs, are complex, logistically challenging, and can be expensive to deliver, but these matters are offset by the perceived benefits of IPE. There is little clarity regarding how IPE contributes to the desirable development of collaborative practitioners. To guide educators in the design of IPE programs there is a need to understand the elements that promote optimal learning. A realist review was conducted to identify the mechanisms and resources that contribute to IPE outcomes. Four databases were searched until April 2020 for empirical studies describing mandatory IPE for pre-registration medical, nursing and other health professional students. Twelve articles met the inclusion criteria. Two novel learning design elements were identified; interdependence, where there is a need for genuine contribution of skills and knowledge from the professions learning together to successfully complete tasks, and embodiment, where through being immersed in an authentic scenario, learners feel what it is like to work in their professions. Other observations supported previous research findings such as the importance of skilled facilitators to promote interaction and reflection. Interprofessional interventions incorporating these specific learning design features seem likely to enhance the impact of IPE, thus making the best use of limited institutional resources and student time.